Analisis Kebutuhan dalam Rekonstruksi RPS Mata Kuliah Bahasa Indonesia di Universitas Katolik De La Salle Manado - Evi Martika D. Kasiahe; Edino A. Lomban; Fabyana I. Tamboto (STIKes Ibnu Sina Ajibarang, 2023)
The problem of Indonesian learning at higher education institutes has been encountered by Indonesian language instructors. The lack of animosity of students to learn Indonesian language and lack of variation in learning methods are one of the main problems occurred. These may cause the Indonesian language learning not to meet the expectation of instructors and students. Indonesian language course has an important goal to improve the students’ language skills and to develop a deep affection for the Indonesian language. One of the methods that may be used in order to handle this problem is needs analysis. This method is expected to accommodate students’ needs pertaining to Indonesian language learning in several study programs at De La Salle Catholic University. The findings of this research will be a reference for the syllabus reconstruction process of Indonesian Language course in order to improve the quality of language learning and to achieve the goals of learning. This syllabus reconstruction consists of several components, namely learning objectives, materials, learning method, and assessment. Pertaining to the components, the results of this research showed that (1) the learning objectives of Indonesian Language course in university cannot be limited to writing skills developments, but can be included also with speaking skills; (2) in materials, the scientific genre and spelling also need to be emphasized; (3) students recommend to use the problem-based learning method, especially for grammar error cases; and (4) the assessment of Indonesian language needs to be designed not only in the form of assignments, but also in the form of objectives and/or essays in accordance with the criterion of HOTS.